A theoretical model of water and trade. (March 2016) - Dang, Qian; Konar, Megan; Reimer, Jeffrey J.; Di Baldassarre, Giuliano; Lin, Xiaowen; Zeng, Ruijie
Highlights: A theoretical model that captures key tradeoffs in water resources use is presented. Conditions under which trade liberalization impact domestic water use are shown. A water tax and subsidies to agricultural capital are policy mechanisms to reduce water use. Risk in water supplies impacts farmer decision-making, reducing water use. Abstract: Water is an essential input for agricultural production. Agriculture, in turn, is globalized through the trade of agricultural commodities. In this paper, we develop a theoretical model that emphasizes four tradeoffs involving water-use decision-making that are important yet not always considered in a consistent framework. One tradeoff focuses on competition for water among different economic sectors. A second tradeoff examines the possibility that certain types of agricultural investments can offset water use. A third tradeoff explores the possibility that the rest of the world can be a source of supply or demand for a country's water-using commodities. The fourth tradeoff concerns how variability in water supplies influences farmer decision-making. We show conditions under which trade liberalization affect water use. Two policy scenarios to reduce water use are evaluated. First, we derive a target tax that reduces water use without offsetting the gains from trade liberalization, although important tradeoffs exist between economic performance and resource use. Second, we show how subsidization of water-saving technologies can allow producers to use less water without reducing agricultural production, making such subsidization an indirect means of influencing water use decision-making. Finally, we outline conditions under which riskiness of water availability affects water use. These theoretical model results generate hypotheses that can be tested empirically in future work.